Essentials of food process engineering - Rao, Chandra Gopala (Boca Raton, FL : CRC Press, 2009)
Covers topics like mass and energy balance, heat and mass transfer and psychrometry and refrigeration
India : BS Publication, 2006
Keywords: Food industry and trade; Food processing plants